Investigation of the Effect of Heat Treatment on the Microstructures and Mechanical Properties of Al-13Si-5Cu-2Ni Alloy - Zhi-Fa Wang; Tian-Jing Miao; Shu-Qing Kou; Shuang Zhang; Feng Qiu (Metals, 2021)
An experimental investigation was carried out to study the effects of solid solution treatment and aging treatment on the microstructures and mechanical properties of an Al-13Si-5Cu-2Ni alloy. The results show that the size of eutectic silicon decreased with solid solution treatment temperature increasing until 510 °C. Subsequently, the eutectic silicon size continued to increase as the temperature increased to 520 °C. Initially, the acicular eutectic silicon of the as-cast alloy was 10.1 μm in size. After the solid solution treatment at 510 °C, the eutectic silicon size was reduced to 6.5 μm. The θ′ phase is the main strengthening phase in the alloy, therefore, the effect of aging treatment on θ′ phases was explored. As the aging time increased, the diameter, length, and fraction volume of the θ′ phases were found to increase. The main reason for the improved performance of this alloy following heat treatment is the passivation spheroidization of the silicon phase and Orowan strengthening due to the θ′ phases. The optimal tensile strength of an Al-13Si-5Cu-2Ni alloy was obtained after solid solution treatment at 510 °C for 8 h followed by an aging treatment at 165 °C for 8 h. Therefore, this work has great significance for promoting the application of Al alloys at high temperatures.